(3GdGJLGgGJ GdeYGUQI aj GOGQI GdeTJQjGJ h GdeNGRf (B/s - (3GdfOGhj, YHO GdYRjR HOQs ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2010)
1)(3GOGQI GdehGO (B: (3eaGgje GOGQjI aj eLGd GdGOGQI h GdCYeGd , GOGQI GdehGO , (B2) (3hXjaI GdTQGA(B: (3JfXje h GOGQI GdTQGA , GdTQGA HGdLhOI GdefGSHI h HGdcejI GdefGSHI , GdTQGA HGdSYQ h GdhbJ GdefGSH (B3) (3GOGQI GdeNGRf (B: (3eaGgje Mhd GdNRjf h GOGQI GdeNGRf , GdQbGHI Ydi GdeNRhf , GLQGAGJ GdNRjf (B.s
(3eQGLY U(B.239 (3; agQS GdGTcGd U(B.14s
Keywords: (3COGQI GdeHjYGJs; (3GdTQGAs